Dissection of Central Carbon Metabolism of Hemoglobin-Expressing Escherichia coli by (13)C Nuclear Magnetic Resonance Flux Distribution Analysis in Microaerobic Bioprocesses - Frey, Alexander D. (American Society for Microbiology, 2001)
Escherichia coli MG1655 cells expressing Vitreoscilla hemoglobin (VHb), Alcaligenes eutrophus flavohemoprotein (FHP), the N-terminal hemoglobin domain of FHP (FHPg), and a fusion protein which comprises VHb and the A. eutrophus C-terminal reductase domain (VHb-Red) were grown in a microaerobic bioreactor to study the effects of low oxygen concentrations on the central carbon metabolism, using fractional (13)C-labeling of the proteinogenic amino acids and two-dimensional [(13)C, (1)H]-correlation nuclear magnetic resonance (NMR) spectroscopy. The NMR data revealed differences in the intracellular carbon fluxes between E. coli cells expressing either VHb or VHb-Red and cells expressing A. eutrophus FHP or the truncated heme domain (FHPg). E. coli MG1655 cells expressing either VHb or VHb-Red were found to function with a branched tricarboxylic acid (TCA) cycle. Furthermore, cellular demands for ATP and reduction equivalents in VHb- and VHb-Red-expressing cells were met by an increased flux through glycolysis. In contrast, in E. coli cells expressing A. eutrophus hemeproteins, the TCA cycle is running cyclically, indicating a shift towards a more aerobic regulation. Consistently, E. coli cells displaying FHP and FHPg activity showed lower production of the typical anaerobic by-products formate, acetate, and d-lactate. The implications of these observations for biotechnological applications are discussed.